Тело человека - Мирошниченко Дарья Александровна (101 факт, который интересно знать, 2021)
Экземпляры: ф.18 (2024) / Инвентарный номер: 60249 / Цена: / Сис.шифр: 28.706я2 / Авт.знак: Т 31 / ББК: 28.706